1982
DOI: 10.1002/zoo.1430010403
|View full text |Cite
|
Sign up to set email alerts
|

Focal palatine erosion associated with dental malocclusion in captive cheetahs

Abstract: A severe palatine disorder caused by maloccluded molars was discovered in captive adult cheetahs at the San Diego Wild Animal Park. This defect has been labeled focal palatine erosion (FPE). Subsequently, a total of 59 cheetahs from several institutions have been examined to evaluate the occurrence and etiology of this disorder. Maloccluded lower molars contacting the palatal mucosa appear to be the primary source of irritation. Infection develops when decaying food and grass particles become lodged in the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
3
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 7 publications
2
66
3
3
Order By: Relevance
“…Outra hipótese a ser verificada é a possibilidade de transmissão genética dessas características, no caso de se tratar de um mesmo ramo familiar. Nisso concordam Fitch & Fagan (1982), que em estudo realizado com guepardos, levantaram a hipótese de que quase todos os casos de erosão palatina focal (FPE) descritos na espécie podem ter sido herdados, sugerindo fatores genéticos, uma vez que foram encontrados em animais importados de uma mesma área do sudoeste da África em 1970, ou dos seus descendentes. Com relação a traumas, Rossi Junior (2002, 2007) e Lopes (2008, inferem que a localização anatômica e o tamanho dos dentes podem predispor a diferentes forças durante sua utilização, levando a fraturas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Outra hipótese a ser verificada é a possibilidade de transmissão genética dessas características, no caso de se tratar de um mesmo ramo familiar. Nisso concordam Fitch & Fagan (1982), que em estudo realizado com guepardos, levantaram a hipótese de que quase todos os casos de erosão palatina focal (FPE) descritos na espécie podem ter sido herdados, sugerindo fatores genéticos, uma vez que foram encontrados em animais importados de uma mesma área do sudoeste da África em 1970, ou dos seus descendentes. Com relação a traumas, Rossi Junior (2002, 2007) e Lopes (2008, inferem que a localização anatômica e o tamanho dos dentes podem predispor a diferentes forças durante sua utilização, levando a fraturas.…”
Section: Discussionunclassified
“…Quanto ao grau, as amostras derivadas de cativeiro apresentaram o dobro de ocorrência de coeficientes mais elevados, quando comparados com os de vida livre. Neste caso, concorda-se relato em literatura de que a etiologia da maioria das doenças orais está relacionada com características físicas de sua dieta e às mudanças químicas a que estas dietas induzem (Fitch & Fagan 1982). Erosão de esmalte foi encontrada em 24,72% dos mãos-peladas examinados e foi mais prevalente nos dentes incisivos e caninos, o que diferiu de Rossi Junior (2002), que relatou baixa incidência dessa lesão, afetando principalmente caninos e pré--molares.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The main physical health problem resulting from such diets is poor oral health. Fitch & Fagan (1982), in their survey, reported that 70 ?& of captive cheetahs fed on soft textured diets had developed focal palatine erosion. They found that this condition was caused by maloccluded dentition, resulting in tooth tips making contact with the soft palate each time the mouth was closed.…”
Section: Feeding Soft Textured Dietsmentioning
confidence: 99%
“…This has obvious implications for the re-introduction of captive carnivores. Fitch & Fagan (1982) noted that captive cheetah would not chew bones unless there was meat attached to them. Offering of bones or dog chews, therefore, is unlikely to alleviate such problems for certain species of zoo-housed carnivores.…”
Section: Feeding Soft Textured Dietsmentioning
confidence: 99%